A Hybrid Mean Value Involving Dedekind Sums and the General Exponential Sums - Jianghua Li; Tingting Wang (The Scientific World Journal)
The main purpose of this paper is using the analytic method, A. Weil’s classical work for the upper bound estimate of the general exponential sums, and the properties of Gauss sums to study the hybrid mean value problem involving Dedekind sums and the general exponential sums and give a sharp asymptotic formula for it.